Architecture now! : houses. - Jodidio, Philip, 1954- (Köln : Taschen, 2009)
Houses Of Today, Built For Tomorrow. New houses of elegance and distinction from around the world. Beyond the fundamental notion of shelter, what defines a house? What are its elements and limitations? This broad-ranging selection of extraordinary dwellings shows the concept to be infinitely malleable: one house seems to hover above the ground, another is embedded in it; some have stark minimal lines, others have tropical gardens; some are palatial, others monastic. From postmodern castles to hi-tech cabins, here is a connoisseur's choice of the world's most remarkable new houses, from deepest Patagonia to the Sydney suburbs, via the USA, Europe, Scandinavia and Asia. Featured architects/firms/artists include: 3LHD Architects, Ábalos & Herreros, Ricardo Bak Gordon, Shigeru Ban, Blank Studio, Gianni Botsford, Nancy Copley, Correia/Ragazzi Arquitectos, Durbach Block, Eastern Design Office, Fuhrimann & Hächler, Terunobu Fujimori, Sou Fujimoto Architects, Kotaro Ide, Carlos Jiménez, Jouin Manku, Kamayachi + Harigai, Mathias Klotz, Kengo Kuma, Leven Betts Studio, MOS, Mount Fuji Architects Studio, Plasma Studio, Antoine Predock, Laurent Savioz, Shim + Sutcliffe, Álvaro Siza Vieira, Philippe Stuebi, Zhang Lei, René van Zuuk and many others.
Keywords: Bouwkunst